JARINGAN SOSIAL PEDAGANG PENDATANG DI PASAR SELASA KECAMATAN TAMPAN - Siadari, Sandhri W; Tantoro, Swis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Pasar Selasa Panam or often referred to as the Pasar Selasa community is one of the traditional markets located on the HR road. Soebrantas Simpang Baru Panam, Pekanbaru City. Initially, the Pasar Selasa was just a shock market which was open every Tuesday, but as the market went on Tuesday the community was very interested so that demand was getting higher, due to the increasing public demand, the Pasar Selasa was open every day and many traders saw this opportunity to make a living no exception the merchant who came from outside the Panam area. The presence of immigrant sellers at the Pasar Selasa is a special concern on how newcomers can trade on the Pasar Selasa. Through Robert D. Putnam's theory, the theory of social capital explains that there is social capital that occurs among the migrant warriors on the Pasar Selasa. Through social capital owned by migrant traders, it can be explained that migrant workers have a social network in the process of being able to trade on the Pasar Selasa. The social networks owned by migrant warriors on the Tuesday Market provide access to migrant traders to be able to fly on the Pasar Selasa. Keywords: Market, Traders, Social Capital